Towards System-Wise Synthetic Inertia Models to Study Power System Frequency Response - Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2017)
Various models have been proposed to analyze the impact of synthetic inertia on frequency response. On one hand, the models that are detailed and realistic in terms power system impact normally overlook detailed representation of inertia emulation, which prevents the analysis of the impact of different control/optimization synthetic inertia policies on power systems. On the other hand, systematic detailed model formulation of the dynamics of turbine, drive and power conversion allowing the analysis of control/optimization synthetic inertia policies are focused on the functioning of the generating units, overlooking a realistic representation of the power system. This paper presents a state space model to represent the frequency dynamics of a realistic power system, including the synthetic inertia in wind turbines. Case studies are simulated to demonstrate that the model response is like the current systems. © 2017 IEEE.